The meaning of Ved. bhari and the comparison with Hitt. parh- and DPerwa- Die Bedeutung von ved. bhari und der Vergleich mit heth. parh- und DPerwa- - Oettinger, Norbert (Historische Sprachforschung, 2020)
Ved. bhari means ‘to stamp, to trample’. This meaning confirms the disputed relationship with Hitt. parh-mi ‘to chase, to hunt’ and its derivation from PIE *bherh2-. The Hittite text KUB 35.145 mentions the god Perwa- beside parhant- ‘chased’ in a characteristic situation. Therefore it is possible that Perwa- and parh-mi are also related. Under these circumstances the most likely reconstruction of Perwa- is *bhḗrh2uo- (or *bhérh2uo-) ‘the chasing one’, denoting a god of wild animals. In this regard it is remarkable that all three, bhari, parh-mi and Perwa-, are connected with horses. The laryngeal in *bhḗrh2uohas been deleted like in *h1erh2ueh2 > *h1erueh2 > *erā in Gr. ἔραζε ‘on the earth‘.
CRIS-Team Scopus Importer:2024-12-16